Integrin Targeting and Beyond: Enhancing Cancer Treatment with Dual-Targeting RGD (Arginine–Glycine–Aspartate) Strategies - Bojana Bogdanović; Daniel Fagret; Catherine Ghezzi; Christopher Montemagno (Pharmaceuticals)
Integrins, an important superfamily of cell adhesion receptors, play an essential role in cancer progression, metastasis, and angiogenesis, establishing them as prime targets for both diagnostic and therapeutic applications. Despite their significant potential, integrin-targeted therapies have faced substantial challenges in clinical trials, including variable efficacy and unmet high expectations. Nevertheless, the consistent expression of integrins on tumor and stromal cells underscores their ongoing relevance and potential. Traditional RGD-based imaging and therapeutic agents have faced limitations, such as inconsistent target expression and rapid systemic clearance, which have reduced their effectiveness. To overcome these challenges, recent research has focused on advancing RGD-based strategies and exploring innovative solutions. This review offers a thorough analysis of the latest developments in the RGD–integrin field, with a particular focus on addressing previous limitations. It delves into new dual-targeting approaches and cutting-edge RGD-based agents designed to improve both tumor diagnosis and therapeutic outcomes. By examining these advancements, this review illuminates new pathways for enhancing the specificity and efficacy of integrin-targeted therapies, paving the way for more effective cancer diagnosis and treatment strategies.